Evaluation of a joint workshop on study design for hospital and community pharmacists: a retrospective cross-sectional survey - Yuki Asai; Yasushi Takai; Toshiki Murasaka; Tomohiro Miyake; Tomohisa Nakamura; Yoshihiko Morikawa; Yuji Nakagawa; Tatsuya Kanayama; Yasuharu Abe; Naoki Masuda; Yasushi Takamura; Yoshihiro Miki; et al. (BMC, 2024)
Abstract Background Although pharmacists often identify numerous clinical questions, they face several barriers, including the lack of mentors for research activities in clinical settings. Therefore, a workshop for the appropriate selection of a study design, which is a fundamental first step, may be necessary. The purpose of this study was to evaluate the effectiveness of a workshop on study design for hospital and community pharmacists. Moreover, the characteristics of pharmacists with little involvement in research activities were extracted using decision-tree analysis to guide the design of future workshops. Methods A workshop was conducted on October 1, 2023. It comprised three parts: lectures, group work, and presentations. Questionnaire-based surveys were conducted with workshop participants regarding their basic information, their background that influenced research activities, their satisfaction, and their knowledge/awareness. For the questions on knowledge/awareness, the same responses were requested before and after the workshop using a five-scale scoring system. Multivariate logistic regression analysis was conducted to identify independent factors influencing research activities. Decision tree analysis was performed to extract low-effort characteristics of the research activities. Results Of the 40 workshop attendees, the overall satisfaction score for the workshop was 4.38 of 5, and the score for each question was 4 or higher. Significant increases were observed in the scores of knowledge/awareness after the workshop. Moreover, 95% of the pharmacists answered that it would be highly useful to conduct a joint workshop between hospitals and community pharmacists. Although independent influencing factors were not detected in the multivariate logistic regression analysis, the decision tree analysis revealed that pharmacists who were no member of an academic society (85%, 11/13) or members without any certifications or accreditations related to pharmacy practice (80%, 4/5) were the least active in clinical research. In contrast, those belonging to academic societies and holding certifications or accreditations related to pharmacy practice frequently conducted clinical research. Conclusion The present study revealed that a joint workshop on study design may have the potential to change pharmacists' knowledge and awareness of research activities. Moreover, future workshops should be conducted with pharmacists who do not belong to academic societies.